A new species of the genus Linoderus Sharp, 1885 (Coleoptera, Staphylinidae, Philonthina) from the Colombian Andes - López-García, Margarita M.; Méndez-Rojas, Diana M. (Zootaxa, 2014)
The monotypic genus Linoderus Sharp, 1885 was described based on a species from Panama and since the original description nearly nothing has been added to its taxonomical knowledge. The aim of the present paper is to describe a new species of the genus from Colombia and to report the genus for the first time from South America, adding some biological notes of the species.